CONVEYOR MODIFICATION BASED ON EMERGENCY STOP INDICATORS AT ISKANDAR PANGKALAN BUN AIRPORT - Muh. Ariandhika Rifqi AS; Kurniaty Atmia; Djunaedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The conventional conveyor system at Iskandar Pangkalan Bun Airport has limitations in terms of operational efficiency and safety, particularly related to the lack of an integrated emergency stop indicator. This study aims to design, implement, and evaluate a conveyor modification by adding an emergency stop indicator system integrated with an Arduino Mega 2560 microcontroller, relay, contactor, buzzer, LED, DS3231 RTC module, and SD Card module. Applied Research and Development (R&D) methods were used in all stages, from design to testing. The test results showed that the emergency stop indicator system achieved a 100% reliability level in stopping the conveyor completely, with an average response time of less than 1 second. Visual and audio indicators were activated instantly (<0.1 seconds), ensuring the emergency warning was effectively communicated. Furthermore, the time-of-event recording to the SD Card functions well, providing accurate historical documentation. This modification proved effective in improving occupational safety and reducing potential damage to conveyors in the airport environment